2007
DOI: 10.1186/1471-2199-8-29
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between ATM and PARP-1 in response to DNA damage and sensitization of ATM deficient cells through PARP inhibition

Abstract: ATM and PARP-1 are two of the most important players in the cell's response to DNA damage. PARP-1 and ATM recognize and bound to both single and double strand DNA breaks in response to different triggers. Here we report that ATM and PARP-1 form a molecular complex in vivo in undamaged cells and this association increases after γ-irradiation. ATM is also modified by PARP-1 during DNA damage. We have also evaluated the impact of PARP-1 absence or inhibition on ATM-kinase activity and have found that while PARP-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 26 publications
5
113
0
Order By: Relevance
“…ATM activation has been proposed to result from changes in chromatin structure, independently of DNA damage (Bakkenist and Kastan, 2003;Soutoglou and Misteli, 2008), a phenomenon that probably occurs in PARG KD cells, supported by the established role of PAR in the modulation of chromatin superstructure. In addition, a functional interplay between PARP1 activity and ATM activity has been reported (Aguilar-Quesada et al, 2007;Haince et al, 2007), supporting the correlation between PAR accumulation and ATM activation observed in PARG-depleted cells.…”
Section: Protective Effect Of Par Spontaneously Produced In Pargdeplesupporting
confidence: 66%
“…ATM activation has been proposed to result from changes in chromatin structure, independently of DNA damage (Bakkenist and Kastan, 2003;Soutoglou and Misteli, 2008), a phenomenon that probably occurs in PARG KD cells, supported by the established role of PAR in the modulation of chromatin superstructure. In addition, a functional interplay between PARP1 activity and ATM activity has been reported (Aguilar-Quesada et al, 2007;Haince et al, 2007), supporting the correlation between PAR accumulation and ATM activation observed in PARG-depleted cells.…”
Section: Protective Effect Of Par Spontaneously Produced In Pargdeplesupporting
confidence: 66%
“…Here, SCGE analysis suggested that the higher PARP activity ( Figure 7A) in Ta-sro1 OE transgenic plants helped maintain DNA integrity by enhancing the activity of the DNA repair machinery (Figure 10). In mammalian cells, PARP-1 could interact directly with ATM (for Ataxia-Telangiectasia mutated), an important sensor of ROS (Guo et al, 2010), and form a large protein complex to function in DNA repair and maintenance of genomic integrity through its PARP activity (Aguilar-Quesada et al, 2007;Gagné et al, 2008). In our study, At-ATM had a higher expression level in Arabidopsis Ta-sro1 OE lines than in the VC line under both NaCl and H 2 O 2 treatments (Supplemental Figure 10).…”
Section: D) (E) To (H) Root Growth and H 2 O 2 Content In Seedlings mentioning
confidence: 53%
“…One speculative possibility is that ROS-induced DNA damage and PARP-1 overactivation caused mitochondrial dysfunction and Ca 2+ release, thereby activating AMPK [14]. Other possibility that may explain how PARP-1 connects with the AMPK/mTOR signaling (besides the maintenance of the energy status) is that PARP inactivation leads to unefficient ATM response that has been reported to be involved in the activation of AMPK [26,27].…”
Section: Discussionmentioning
confidence: 99%